U/Th systematics and ages of authigenic carbonates from Hydrate Ridge, Cascadia Margin: Recorders of fluid flow variations - Teichert, Barbara; Eisenhauer, Anton; Bohrmann, G; Haase, Alexandra; Bock, Barbara; Linke, Peter (Geochimica Et Cosmochimica Acta, 2003)
Uranium (U) concentrations and activity ratios (δU) of authigenic carbonates are sensitive recorders of different fluid compositions at submarine seeps of hydrocarbon-rich fluids ("cold seeps") at Hydrate Ridge, off the coast of Oregon, USA. The low U concentrations (mean: 1.3 ± 0.4 μg/g) and high δU values (165-317‰) of gas hydrate carbonates reflect the influence of sedimentary pore water indicating that these carbonates were formed under reducing conditions below or at the seafloor. Their Th/ U ages span a time interval from 0.8 to 6.4 ka and cluster around 1.2 and 4.7 ka. In contrast, chemoherm carbonates precipitate from marine bottom water marked by relatively high U concentrations (mean: 5.2 ± 0.8 μg/g) and a mean δU ratio of 166 ± 3‰. Their U isotopes reflect the δU ratios of the bottom water being enriched in U relative to normal seawater. Simple mass balance calculations based on U concentrations and their corresponding δU ratios reveal a contribution of about 11% of sedimentary pore water to the bottom water. From the U pore water flux and the reconstructed U pore water concentration a mean flow rate of about 147 ± 68 cm/a can be estimated. Th/U ages of chemoherm carbonates range from 7.3 to 267.6 ka. Th/U ages of two chemoherms (Alvin and SE-Knoll chemoherm) correspond to time intervals of low sealevel stands in marine isotope stages (MIS) 2, 4, 5, 6, 7 and 8. This observation indicates that fluid flow at cold seep sites sensitively reflects pressure changes of the hydraulic head in the sediments. The δO ratios of the chemoherm carbonates support the hypothesis of precipitation during glacial times. Deviations of the chemoherm δO values from the marine δO record can be interpreted as to reflect temporally and spatially varying bottom water and/or vent fluid temperatures during carbonate precipitation between 2.6 and 8.6°C. Copyright © 2003 Elsevier Ltd.